2001
DOI: 10.1074/jbc.m106161200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction of the Spinal Muscular Atrophy Disease Protein SMN with the Small Nucleolar RNA-associated Protein Fibrillarin

Abstract: Fibrillarin is one of four proteins known to interact selectively with all Box C/D family small nucleolar (sno) 1 RNAs (1-6). In eukaryotes, large numbers of snoRNAs direct cleavages and specific nucleotide modifications of pre-rRNA that are required for ribosome biogenesis (7-11). Most Box C/D family snoRNAs guide the site-specific 2Ј-O-methylation of rRNA (12,13). snoRNAs function as RNA-protein complexes known as small nucleolar ribonucleoprotein particles (snoRNPs) (11,14).Fibrillarin has sequence and stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
139
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 69 publications
4
139
0
Order By: Relevance
“…SMN also binds directly to fibrillarin and GAR1, constituents of box C/D and box H/ACA small nucleolar RNPs (snoRNPs), respectively (Jones et al 2001;Pellizzoni et al 2001a). In vitro binding assays performed with full-length and truncated forms of the protein showed that SMN interacts directly with both fibrillarin and GAR1 and that the interactions are mediated by the RG-rich domains of fibrillarin and GAR1.…”
Section: A Role For the Smn Complex In The Biogenesis Of Other Rnpsmentioning
confidence: 99%
“…SMN also binds directly to fibrillarin and GAR1, constituents of box C/D and box H/ACA small nucleolar RNPs (snoRNPs), respectively (Jones et al 2001;Pellizzoni et al 2001a). In vitro binding assays performed with full-length and truncated forms of the protein showed that SMN interacts directly with both fibrillarin and GAR1 and that the interactions are mediated by the RG-rich domains of fibrillarin and GAR1.…”
Section: A Role For the Smn Complex In The Biogenesis Of Other Rnpsmentioning
confidence: 99%
“…The N-terminal fragment of fibrillarin contains the glycine-and arginine-rich (GAR) domain (Fig. 4A) (25,26) responsible for interaction with other proteins such as spinal muscular atrophy disease protein (27). A deletion mutant, where the GAR domain was removed from GST-fibrillarin ( Fig.…”
Section: Orf3 Protein Does Not Localize To the Nucleolus In Fibrillarmentioning
confidence: 99%
“…FIB co-localizes with the survival motor neuron (SMN) gene product in both nucleoli and Cajal bodies/gems of primary neurons (19,20). SMN is linked to one of the most common inheritable causes of childhood mortality, spinal muscular atrophy (19). In fact, a direct interaction between FIB and SMN has been demonstrated, although no functional basis for this interaction has been established, including any involvement of FIB in the pathogenesis of spinal muscular atrophy.…”
mentioning
confidence: 99%
“…The GAR domain is methylated at arginine residues, although the arginine methyltransferase responsible for in vivo methylation has not been identified (23,24). The GAR domain is responsible for the interaction of FIB with both SMN protein and the DEAD box RNA helicase p68 (19,21). A centrally located 90-residue sequence resembles an RNA-binding domain (RBD) present in various snRNPs.…”
mentioning
confidence: 99%
See 1 more Smart Citation